2016
DOI: 10.1108/jocm-09-2015-0154
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the perceived value of social practice theories for business-to-business marketing managers

Abstract: Structured AbstractPurpose: Drawing on sociological theories of Giddens, Bourdieu and Goffman, we explore how different relationships are characterized between actors in interaction and determine whether social theories of practice resonate as being practical to business marketers. Design/methodology/approach: In our empirical investigations, we employ the Delphi Method whereby we 'elevate' 6 highly experienced marketing practitioners in Dubai and Bangkok, each in different industries and from different cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
(68 reference statements)
0
12
0
2
Order By: Relevance
“…However, this might not be possible under pressure of time and resource constraints. This is at odds with what Ardley and Quinn (2014) suggest happens and Lowe et al (2016) have observed with respect to professional practice in busy operational contexts. However, in using the paradigm mapping of Lowe et al (2004) some of these conceptual issues at least might be straightened out.…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…However, this might not be possible under pressure of time and resource constraints. This is at odds with what Ardley and Quinn (2014) suggest happens and Lowe et al (2016) have observed with respect to professional practice in busy operational contexts. However, in using the paradigm mapping of Lowe et al (2004) some of these conceptual issues at least might be straightened out.…”
Section: Resultsmentioning
confidence: 70%
“…Interestingly, what Rossiter (2012) recommends as a methodological corrective almost parallels what Lowe et al (2016) discovered from a social practice perspective but in reverse. Rossiter (2012) is saying that marketers should work systematically and use empirical processes carefully but when in doubt default to using the established model and deductive logic for strategic guidance with respect to advertising and marketing.…”
Section: Lowe's Paradigm Mapping Categories As Descriptorsmentioning
confidence: 88%
See 3 more Smart Citations